2017
DOI: 10.2140/involve.2017.10.151
|View full text |Cite
|
Sign up to set email alerts
|

Loewner deformations driven by the Weierstrass function

Abstract: The Loewner differential equation provides a way of encoding growing families of sets into continuous real-valued functions. Most famously, Schramm-Loewner evolution (SLE) consists of the growing random families of sets that are encoded via the Loewner equation by a multiple of Brownian motion. The purpose of this paper is to study the families of sets encoded by a multiple of the Weierstrass function, which is a deterministic analog of Brownian motion. We prove that there is a phase transition in this setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Since this function is continuous but nowhere differentiable, it serves as a deterministic analogue of Brownian motion. Similar to SLE, the Loewner hulls driven by c W , studied in [17], have a phase transition. In particular for c small enough c W generates simple curves, but for c large enough the hulls are not simple.…”
Section: Examples Of Time-changed Deterministic Functionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Since this function is continuous but nowhere differentiable, it serves as a deterministic analogue of Brownian motion. Similar to SLE, the Loewner hulls driven by c W , studied in [17], have a phase transition. In particular for c small enough c W generates simple curves, but for c large enough the hulls are not simple.…”
Section: Examples Of Time-changed Deterministic Functionsmentioning
confidence: 95%
“…In particular for c small enough c W generates simple curves, but for c large enough the hulls are not simple. In [17], it is also shown that near a local maximum W t grows faster than an appropriately scaled square root curve. Therefore, Theorem 4.1(b) implies that c W (E t ) does not generate a simple curve.…”
Section: Examples Of Time-changed Deterministic Functionsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first statment can be established by a short computation (see, for instance, [LRob,Lemma 2.3]). The second statement follows from a comparison between the driving functions λ and k √ 1 − t (see, for instance, [LRob,proof of Theorem 1.1]).…”
Section: Loewner Equation Backgroundmentioning
confidence: 99%
“…The first statment can be established by a short computation (see, for instance, [LRob,Lemma 2.3]). The second statement follows from a comparison between the driving functions λ and k √ 1 − t (see, for instance, [LRob,proof of Theorem 1.1]). While Lemma 2.1 can be used to determine when a Loewner hull is not a simple curve, the following theorem gives a large class of hulls that are simple curves.…”
Section: Loewner Equation Backgroundmentioning
confidence: 99%